2018
DOI: 10.1186/s13075-018-1644-6
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of depression in axial spondyloarthritis and its association with disease activity: a systematic review and meta-analysis

Abstract: BackgroundDepression is common among patients with axial spondyloarthritis (axSpA), but reports of its prevalence are highly variable. We performed a systematic review to (i) describe the prevalence of depression in axSpA, (ii) compare its prevalence between axSpA, ankylosing spondylitis (AS) and non-radiographic axSpA (nr-axSpA) cohorts, and (iii) compare disease activity and functional impairment between those with and without depression.MethodsWe searched Medline, PubMed, Web of Science, PsycINFO, CINAHL Pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
110
1
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(130 citation statements)
references
References 37 publications
14
110
1
5
Order By: Relevance
“…Depression and fibromyalgia were not described in ASAS-COMOSPA. The prevalence of depression reported in our cohort was very similar to results from a prior meta-analysis in axSpA (16% vs 15%) [25]. Fibromyalgia (5%) was likely under-diagnosed, compared to prevalence reported using meta-analysis (13%) and found by screening questionnaire in the British Society for Rheumatology Biologics Register for AS (21%) [26,27].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Depression and fibromyalgia were not described in ASAS-COMOSPA. The prevalence of depression reported in our cohort was very similar to results from a prior meta-analysis in axSpA (16% vs 15%) [25]. Fibromyalgia (5%) was likely under-diagnosed, compared to prevalence reported using meta-analysis (13%) and found by screening questionnaire in the British Society for Rheumatology Biologics Register for AS (21%) [26,27].…”
Section: Discussionsupporting
confidence: 85%
“…Associations between clusters dominated by these two conditions and patient-reported outcome measures were similar in magnitude to those reported in other studies [25][26][27]7]. In previous meta-analysis, depression was additionally associated with objective measures such as ESR and the Bath AS metrology index [25]. Baseline depression has also been shown to reduce treatment response in RA [28] but further studies are needed in axSpA.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In their 2018 systematic review, Zhao et al (14) identified 16 studies and reported the prevalence of depression ranging from 11% to 64% and pooled prevalence of 0.29 (95% 10 CI 0.15 to 0.44), which is consistent with secondary outcomes in our current systematic review. The issue of prevalent (or comorbid) depression is particularly important in AS management, given associations with disease activity and functional impairment (14) as well as the diagnosis delay from the symptom onset (26). Equally important is the onset of depression following AS diagnosis and as we demonstrated in our systematic review, there is a 51% higher risk of depression among AS patients compared to individuals without AS.…”
Section: Discussionsupporting
confidence: 84%
“…To our knowledge, this is the first systematic review on the incidence of depression and/or anxiety among patients with AS, which builds on prior systematic reviews on the prevalence of depression in this patient population (14). In their 2018 systematic review, Zhao et al (14) identified 16 studies and reported the prevalence of depression ranging from 11% to 64% and pooled prevalence of 0.29 (95% 10 CI 0.15 to 0.44), which is consistent with secondary outcomes in our current systematic review. The issue of prevalent (or comorbid) depression is particularly important in AS management, given associations with disease activity and functional impairment (14) as well as the diagnosis delay from the symptom onset (26).…”
Section: Discussionmentioning
confidence: 98%